Colossal Negative Thermal Expansion in Electron‐Doped PbVO3 Perovskites. Issue 27 (11th June 2018) - Yamamoto, Hajime; Imai, Takashi; Sakai, Yuki; Azuma, Masaki
Abstract: Colossal negative thermal expansion (NTE) with a volume contraction of about 8 %, the largest value reported so far for NTE materials, was observed in an electron‐doped giant tetragonal perovskite compound Pb1− x Bi x VO3 ( x =0.2 and 0.3). A polar tetragonal ( P 4 mm ) to non‐polar cubic structural transition took place upon heating. The coefficient of thermal expansion (CTE) and the working temperature could be tuned by changing the Bi content, and La substitution decreased the transition temperature to room temperature. Pb0.76 La0.04 Bi0.20 VO3 exhibited a unit cell volume contraction of 6.7 % from 200 K to 420 K. Interestingly, further gigantic NTE of about 8.5 % was observed in a dilametric measurement of a Pb0.76 La0.04 Bi0.20 VO3 polycrystalline sample. The pronounced NTE in the sintered body should be attributed to an anisotropic lattice parameter change. Abstract : Colossal negative thermal expansion (NTE) with a volume contraction of 6–8 %, the largest value reported for NTE materials, was observed in Pb1− x Bi x VO3 ( x =0.2 and 0.3) and Pb0.76 La0.04 Bi0.20 VO3 . The coefficient of thermal expansion and the working temperature could be tuned by changing the Bi and La content. This finding opens an avenue to designing new NTE materials based on giant tetragonal perovskite materials.